SOCIAL ASPECTS OF MENTAL ILLNESS AND RELATED ETHICAL ISSUES (PREJUDICE, STIGMATISATION)1 - Škoda, Miroslav (Uniwersyteckie Czasopismo Socjologiczne, 2016)
At the beginning the paper introduces the role of patient and the four features of the role, as formulated by T. Parsons and E. Freidson in their sociology works. Based on this concept of the role of the patient, the text argues in favour of recognising the mental illness as a real illness. (This recognition is not obvious and is often disputed.) Next, the paper explains the phenomenon of prejudices, and how they are formed. It is related to the stereotypes and the process of categorisation, and therefore the work presents these terms as well. Some specific examples of prejudice both against the mentally ill and psychiatry as such are also introduced. In the last chapter, the issue of stigma and stigmatisation related to the mental illness is presented. The focus is made on the etymology of the word “stigma” and its current use. The paper aims at clarifying the social status of the mentally ill, who suffer not only from their disease, but also from the above mentioned negative social phenomena such as prejudices and stigmatisation.